Reviewing the evidence base for social recovery in mental health service provision: A protocol for a scoping review. - Calvin Swords; Michael John Norton; Alan Maddock (PLoS ONE)
Introduction The concept of recovery within mental health service delivery is no longer a new concept across the westernised world. However, its development in terms of implementation policy and practice has remained challenging for all stakeholders. This has focused on personal recovery being unattainable for many individuals due to neoliberalism and individualism. Consequently, one argument which is beginning to build is the need to focus on the idea of social recovery, a relatively new concept. However, no synthesis of social recovery's evidence base in relation to mental health service provision has taken place. This protocol provides a detailed plan of how a scoping review would be undertaken and completed to examine this evidence. Methods and analysis Adopting Arksey and O'Malley's framework, A Preferred Reporting Items for Systematic Reviews and Meta-Analysis compliant scoping review has been chosen. This includes a five-stage approach to completing scoping reviews. This includes the search terms that will be used. It also details the variety of databases (CINAHL, EBSCO, Jstor, OVID SP, PsychINFO, PubMed, RCNi, Science Direct, Web of Science and Scopus) and other sources including repositories (Cochrane Online Library, ETHos, nz.research.org.nz, ProQuest, National ETD Portal, Google, Google Scholar and ResearchGate). Inclusion and exclusion criteria are illustrated in this protocol. Given that the concept of social recovery is relatively new, no search range was chosen.